Antioxidant Activities, Phenolic Compounds, and Sensory Acceptability of Kombucha-Fermented Beverages from Bamboo Leaf and Mulberry Leaf - Ruo-Gu Xiong; Si-Xia Wu; Jin Cheng; Adila Saimaiti; Qing Liu; Ao Shang; Dan-Dan Zhou; Si-Yu Huang; Ren-You Gan; Hua-Bin Li (MDPI AG, 2023)
Kombucha is traditional drink made from the fermentation of a black tea infusion, and is believed to offer a variety of health benefits. Recently, exploring kombucha made from alternative substrates has become a research hotspot. In this paper, two novel kombucha beverages were produced with bamboo leaf or mulberry leaf for the first time. Moreover, the effects of fermentation with leaf residues (infusion plus residues) or without leaf residues (only infusion) on the antioxidant properties of kombucha were compared. The ferric-reducing antioxidant power assay, Trolox equivalent antioxidant capacity assay, Folin-Ciocalteu method, and high-performance liquid chromatography were utilized to measure the antioxidant capacities, total phenolic contents, as well as some compound concentrations of the kombucha. The results showed that two types of kombucha had high antioxidant capacities. Moreover, kombucha fermented with bamboo leaf residues (infusion plus residues) significantly enhanced its antioxidant capabilities (maximum increase 83.6%), total phenolic content (maximum increase 99.2%), concentrations of some compounds (luteolin-6-C-glucoside and isovitexin), and sensory acceptability, compared to that without residues (only infusion). In addition, fermentation with leaf residues had no significant effect on mulberry leaf kombucha. Overall, the bamboo leaf was more suitable for making kombucha with residues, while the mulberry leaf kombucha was suitable for fermentation with or without residues.